Pengaruh Model Konseling Behavioral dengan Teknik Self Management dalam Mengatasi Perilaku Membolos Peserta Didik - Anggita Yohana Fransika Purba; Ni Ketut Suarni; Gede Nugraha Sudarsana (Universitas Pendidikan Ganesha, 2022)
This research was conducted to determine the effectiveness of Behavioral counseling services with Self-Management techniques to overcome the truancy behavior of eighth grade students of SMP Negeri 6 Singaraja.” The location of the research was SMP Negeri 6 Singaraja, class VIII 3 with a total of 8 students at SMP Negeri 6 Singaraja. The method used in this research is experimental. Sampling using purposive sampling technique. Collecting data using a truant behavior questionnaire. The data analysis technique used parametric statistical analysis, namely by using the Paired-Sample T-Test test with the help of the SPSS for windows version 16.00 program. This research method aims to determine the effect of individual counseling through a behavioral approach with self-management techniques in overcoming the behavior of truant students. In this research, experimental design is used.